Perspective: Successes and Challenges in Developing a New Biomolecular Modeling and Design Summer High School Research Internship - Vater, Ashley; Caster, Ryan; Haddox, Hugh; Olshefsky, Audrey; Said, Meerit; King, Neil P.; Siegel, Justin B. (Frontiers in Education, 2022)
In response to the limited research experiences for young scholars during the COVID-19 pandemic and community interest, we developed the Pre-College Rosetta Internship Opportunity (PCR-IO). The mission of PCR-IO was to offer a program to increase equitable access to computational biomolecular research. The PCR-IO program engaged rising senior high school students in a protein therapeutic design project in which they produced novel structural models using the PyRosetta and Foldit software packages. The program comprised a year-long series of activities, with an immersive summer internship that involved students in research as the cornerstone. These activities aimed to support the overarching goal of the program by expanding participating students’ social capital and technical skills, making them more likely to consider and succeed in STEM in their future endeavors. Here we describe the program’s components and rollout and discuss successes and challenges in implementing a remote computational research-based educational high school program. We observed considerable student skill development and conclude that the program created real added value to student participants’ education. We also uncovered issues associated with curriculum pace and found that the required mentorship effort exceeded our expectations. This perspective is intended to offer insight, share recommendations, and create dialog to increase propagation of research-based computational internships, and to shed light on how much novice students can accomplish with mentorship, structured curricula, and access to the research community.